RVD induction and autologous stem cell transplantation followed by lenalidomide maintenance in newly diagnosed multiple myeloma: a phase 2 study of the Finnish Myeloma Group - Sini Luoma; Pekka Anttila; Marjaana Säily; Tuija Lundan; Jouni Heiskanen; Timo Siitonen; Sakari Kakko; Mervi Putkonen; Hanna Ollikainen; Venla Terävä; Marja Sankelo; Anu Partanen; et al. (SPRINGER, 2022)
Autologous stem cell transplantation (ASCT) combined with novel agents is the standard treatment for transplant-eligible, newly diagnosed myeloma (NDMM) patients. Lenalidomide is approved for maintenance after ASCT until progression, although the optimal duration of maintenance is unknown. In this trial, 80 patients with NDMM received three cycles of lenalidomide, bortezomib, and dexamethasone followed by ASCT and lenalidomide maintenance until progression or toxicity. The primary endpoint was the proportion of flow-negative patients. Molecular response was assessed if patients were flow-negative or in stringent complete response (sCR). By intention to treat, the overall response rate was 89%. Neither median progression-free survival nor overall survival (OS) has been reached. The OS at 3 years was 83%. Flow-negativity was reached in 53% and PCR-negativity in 28% of the patients. With a median follow-up of 27 months, 29 (36%) patients are still on lenalidomide and 66% of them have sustained flow-negativity. Lenalidomide maintenance phase was reached in 8/16 high-risk patients but seven of them have progressed after a median of only 6 months. In low- or standard-risk patients, the outcome was promising, but high-risk patients need more effective treatment approach. Flow-negativity with the conventional flow was an independent predictor for longer PFS.